2019
DOI: 10.4038/sljb.v4i2.39
|View full text |Cite
|
Sign up to set email alerts
|

Use of ovitrap surveillance to assess dengue outbreak risks in selected dengue endemic areas in Sri Lanka

Abstract: Dengue fever has been endemic to Sri Lanka for several decades. Due to the unavailability of an established prophylactic medicine, dengue prevention depends largely on vector control, where vector surveillance plays a key role. The present study aimed to assess the Aedes mosquito abundance and the risk of disease outbreak using ovitrap surveillance in 14 areas in Sri Lanka, covering four districts with high dengue incidence during 2014 -2016. A total of 1537 ovitraps were placed in Colombo (Kirulapone, Dematag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Another study in Brazil also indicated that data gathered by ovitraps could be used for dengue incidence warning signals up to two months earlier and had a good predictive power for upcoming dengue outbreaks [ 48 ]. This finding was in accordance with a study carried out in Sri Lanka, which examined several area with repeated dengue epidemics, showing that mosquito density depicted in the OI is positively correlated with dengue incidence [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study in Brazil also indicated that data gathered by ovitraps could be used for dengue incidence warning signals up to two months earlier and had a good predictive power for upcoming dengue outbreaks [ 48 ]. This finding was in accordance with a study carried out in Sri Lanka, which examined several area with repeated dengue epidemics, showing that mosquito density depicted in the OI is positively correlated with dengue incidence [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…aegypti prefers indoor breeding to outdoor while Ae. albopictus prefers both indoor and outdoor breeding [ 12 , 22 , 23 ]. Both the feeding and breeding behavior of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…A house which is clean from mosquito nests does not mean free from mosquitoes. Mosquitoes can fly 50-100 m, so mosquitoes can visit our homes from other places [3,6,7]. Puddles of water in house gutters, used goods and garbage that can accommodate rainwater, water storage containers in public places such as mosques, schools, or public buildings are places that mosquito can lay eggs and can act as sources of mosquitoes for the environment [3,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…About three days after the female mosquito sucks blood, she will lay her eggs. Aedes mosquitoes do not fly far, they only fly 50-100 meters during their lifetime, even research in Peru states that Aedes only move about 30 meters, so after sucking blood, mosquitoes tend to lay eggs inside the house [3,6,7,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation